Hubungan Antara Kontrol Diri dengan Kesehatan Mental Mahasiswa di Universitas ‘Aisyiyah Yogyakarta - Erlangga, Arya Dwi (LITERATUS, 2025)
This study aims to examine the relationship between self-control and mental health among students at 'Aisyiyah University Yogyakarta. The study is motivated by the increasing concerns over mental health issues among university students, which can be influenced by various factors, including self-control. Self-control is a critical psychological aspect that can help individuals manage stress, emotions, and behaviors, potentially impacting their overall mental well-being. The research utilized a correlational quantitative approach, involving a sample of students from various faculties at 'Aisyiyah University Yogyakarta. Data were collected using standardized questionnaires assessing self-control and mental health status. The results of the study indicate a significant relationship between self-control and mental health, with students who demonstrate higher levels of self-control reporting